EFFECTS OF TABATA TRAINING ON HEALTH-RELATED FITNESS COMPONENTS AMONG SECONDARY SCHOOL STUDENTS (Kinesiology, 2022)
Physical education curricula in Polish schools should include more tasks to increase physical activity. The Tabata Training Program can help regulate body weight and induce changes in body fat and physical fitness. This study aimed to determine the effects of a 10-week PE curriculum supplemented by a Tabata Training Program on health-related fitness in 16-year-old secondary school students. The study examined 187 students (66 boys and 121 girls) assigned to either a Tabata Training Program intervention or control group. The intervention lasted 14 minutes during one physical education lesson per week. Pre- and post-intervention, anthropometric measurements were taken, and each participant performed physical fitness tests to evaluate muscular strength, flexibility, speed/agility, and cardiovascular efficiency. Boys of the intervention group significantly reduced body fat (by 1.77%, p